Enhanced laser-driven hadron sources with nanostructured double-layer targets. (24th March 2020) - Fedeli, L; Formenti, A; Pazzaglia, A; Arioli, F M; Tentori, A; Passoni, M
Abstract: Laser-driven ion sources are approaching the requirements for several applications in materials and nuclear science. Relying on compact, table-top, femtosecond laser systems is pivotal to enable most of these applications. However, the moderate intensity of these systems ( I ≲ 10 19 W cm −2 ) could lead to insufficient energy and total charge of the accelerated ions. The use of solid foils coated with a nanostructured near-critical layer is emerging as a promising targeted solution to enhance the energy and the total charge of the accelerated ions. For an appropriate theoretical understanding of this acceleration scheme, a realistic description of the nanostructure is essential, also to precisely assess its role in the physical processes at play. Here, by means of 3D particle-in-cell simulations, we investigate ion acceleration in this scenario, assessing the role of different realistic nanostructure morphologies, such as fractal-like foams and nanowire forests. With respect to a simple flat foil, the presence of a nanostructure allows for up to a × 3 increase of the maximum ion energy and for a significant increase of the conversion efficiency of laser energy into ion kinetic energy. Simulations show also that the details of the nanostructure morphology affect both the maximum energy of the ions and their angular distribution. Furthermore, combined 3D particle-in-cell and Monte Carlo simulations show that if accelerated ions are used for neutron generation with a beryllium converter, double-layer nanostructured targets allow to greatly enhance the neutron yield. These results suggest that nanostructured double-layer targets could be an essential component to enable applications of hadron sources driven by compact, table-top lasers.